LGG-02. Cardiac toxicity in patients receiving single-agent MEK inhibition. (3rd June 2022) - Cantor, Evan; Shatara, Margaret; Meyers, Ashley; Ogle, Andrea; McHugh, Michele; Reiners, Stephanie; Cluster, Andrew; Abdelbaki, Mohamed S; Navalkele, Pournima; Brossier, Nicole M
Abstract: BACKGROUND: MEK inhibitor therapy is increasingly being utilized for the treatment of pediatric tumors, including low-grade glioma, plexiform neurofibroma and Langerhans cell histiocytosis. These drugs are well-tolerated but do have risk of toxicity, including cardiac toxicity. The purpose of this study is to better characterize MEK inhibitor-induced cardiac toxicity in pediatric patients. METHODS: Retrospective review of all patients who underwent MEK inhibitor mono-therapy for at least 3 months, 2015- 2021, age 25 years or less, at St. Louis Children's hospital and Cardinal Glennon Children's hospital. RESULTS: We evaluated 31 patients, 19 (61%) with brain tumors and 12 (39%) without. Of the thirty-one, fifteen (48%) had NF1, 1 had Tuberous sclerosis. Cardiac toxicity consisted of asymptomatic sinus tachycardia, bradycardia, or decreased ejection fraction (EF). Thirteen patients (42%) experienced an asymptomatic decrease in left-ventricular ejection fraction (EF), Grade I-III. Time on therapy before decreased EF was 5 days to 21 months, median 2.8 months. Decreased EF developed in 5 of 13 patients receiving selumetinib and 8 of 18 receiving trametinib. Of the patients who developed decreased EF, 11 (85%) had brain tumors, 6 (46%) had NF1, and 89% had received prior systemic therapy. Out of the patients who had received no prior systemic therapy (6), 2 (33%) had decreased EF, while 11/25 (44%) of those who had received prior systemic therapy did. Drug was held temporarily for 6 patients, with dose limiting toxicity for 5 patients. Drug was discontinued for 1 patient after EF continued to decline despite dose reduction. Patients showed improvement in EF as early as 2 weeks after holding therapy. CONCLUSIONS: Cardiac toxicity in our patients was limited to asymptomatic reduction in ejection fraction, sinus bradycardia and tachycardia, reinforcing the need for appropriate monitoring via echocardiography. Prior systemic therapy was associated with decreased EF.